Insulin-Leptin Axis, Cardiometabolic Risk and Oxidative Stress in Elderly with Metabolic Syndrome - Gradinaru, Daniela; Khaddour, Husseina; Margina, Denisa; Ungurianu, Anca; Borsa, Claudia; Ionescu, Cristina; Prada, Gabriel-Ioan; Usher, Joshua; Elshimali, Yahya (Experimental and Clinical Endocrinology & Diabetes, 2018)
Insulin and leptin have an overlapping anorexigenic action as well as opposite effects on glucose and lipid metabolism. The study focuses on the biochemical and clinical relevance of new indices of insulin-leptin axis utilized in the study of the relationships between leptinemia, insulin sensitivity and oxidative stress, in elderly subjects with metabolic syndrome. We conducted clinical studies on elderly people with metabolic syndrome versus control subjects by creating new insulin-adipogenic indices, namely Insulin-to-Leptin Ratio (ILR) and Insulin-Adipogenic Resistance index (IAR-index). Inflammation and oxidative stress biomarkers evaluated were the high-sensitivity C-reactive protein (hsCRP), the advanced oxidation protein products (AOPP), and the serum antioxidant capacity measured as ferric reducing antioxidant potential (FRAP). The metabolic syndrome group showed significantly (p<0.01) lower levels of ILR and not significant (p=0.09) higher values of IAR-index, as compared to the control group. In metabolic syndrome subjects, the IAR-index was significantly positively correlated with uric acid (r=0.313, p<0.05), FRAP (r=0.347, p<0.05) and AOPP (r=0.677, p<0.01), and negatively correlated with HDL-cholesterol (r=− 0.340, p<0.05) as well as with the ratio FRAP/uric acid (r=− 0.315, p<0.05). ILR and IAR-index reflected the biological state of adipose and pancreatic β-cells and seem to depict the adipo-insular axis status related to metabolic and oxidative stress better than individual markers. Therefore, ILR and IAR-index could represent integrated high-potential biomarkers for disease and patient stratification.
Keywords: insulin-leptin axis; metabolic syndrome; oxidative stress; elderly